Τα τοιχογραφημένα παρεκκλήσια της Σκήτης των Καυσοκαλυβίων, Μέρος Α΄ (17ος-18ος αι.) - Καυσοκαλυβίτης Μοναχός Πατάπιος (Μακεδονικά, 2011)
Most of the art work on reserve today at the Skete of Holy Trinity ofKausokalyvia in Mount Athos and its greater area originates in the 18thcentury. During this time the Kyriakon church (second-half of 18th century)as well as the chapels of Koimisis of Theotokos (1759) and St John Theologos(1777) were painted.In the present study, which is composed of two parts, a concise description is being made of the iconographic program of the Skete chapels, while atthe same time the existing historical information regarding the founders, aswell as the painters, is being attached.In the present part A, reference is being made first on the portions offrescoes of the Ypapanti chapel (first half of 17th century) at the St Neiloscell, works that are attributed according to the tradition to St Neilos Mirovlitis(†1651), who lived an ascetic life in a cave at the area.Reference is being made on the chapel of St John Theologos of thehomonymous hermitage of the Skete, where historical and biographical dataabout the church and its founder, hieromonk Paisios of Kausokalyvia (†1801),are being presented. The painter of the church, monk Mitrofanis of Chiosappears, through our research, to have a significant yet unknown work. A listis being attached of the up-to-date signed or attributed to him works in MountAthos, as well as in the island of Skopelos in the North Sporades, Greece. Inaddition, a brief description of the rich iconographic program of the St JohnTheologos chapel (1777) is attached.Finally, reference is being made on the three portions of frescoes, whichexist at the St Maximos Kausokalivis chapel of the homonymous hermitage ofthe Kausokalivia Skete (half of 18th century).